Pollinator probing preference and switching mode-mediated self-interference within a monoecious plant significantly reduced reproductive fitness - Wu, Bi-Xian; Ma, Li-Na; Xia, Nan; Wang, Hao; Cao, Guo-Xing (Frontiers in Plant Science, 2023)
Introduction Monoecy is usually interpreted as an important evolutionary route of the plant sexual system from hermaphroditism to dioecy. This floral mechanism can effectively reduce self-interference during the reproductive process, and the services provided by pollinators may play an essential role in monoecious species; however, relevant research is still lacking. Thus, we aimed to determine whether monoecious plants could effectively avoid self-interference and promote the evolution of monoecy under the service of pollinators. Methods Here, we successfully performed manipulation experiments to test self-compatibility, pollinator behavior, and self-interference between male and female functions in Akebia trifoliata, a typical monoecious species. Results We demonstrated that experimental self-pollination did not yield any fruit, and supplemental pollination significantly increased fruit set and fruit weight compared to natural pollination, suggesting that this species is completely self-incompatible and experiences strong pollen limitation. Simultaneous self- and cross-pollination and self-pollination prior to cross-pollination significantly reduced reproductive fitness, but self-pollination after cross-pollination did not, indicating self-interference in this plant. Moreover, both male flower probing preference and switching modes within inflorescences by pollinators successfully reinforced self-interference and were also responsible for decreasing reproductive fitness in A. trifoliata. Discussion In summary, pollinator-mediated self-interference significantly reduced selfing, providing potential dynamics for the maintenance and evolution of monoecy.